Specific in situ immuno-imaging of pulmonary-resident memory lymphocytes in human lungs - Humphries, Duncan C.; O’Connor, Richard A.; Stewart, Hazel L.; Quinn, Tom M.; Gaughan, Erin E.; Mills, Beth; Williams, Gareth O.S.; Stone, James M.; Finlayson, Keith; Chabaud-Riou, Martine; Boudet, Florence; Dhaliwal, Kevin; et al. (Frontiers in Immunology, 2023)
Introduction Pulmonary-resident memory T cells (TRM) and B cells (BRM) orchestrate protective immunity to reinfection with respiratory pathogens. Developing methods for the in situ detection of these populations would benefit both research and clinical settings. Methods To address this need, we developed a novel in situ immunolabelling approach combined with clinic-ready fibre-based optical endomicroscopy (OEM) to detect canonical markers of lymphocyte tissue residency in situ in human lungs undergoing ex vivo lung ventilation (EVLV). Results Initially, cells from human lung digests (confirmed to contain TRM/BRM populations using flow cytometry) were stained with CD69 and CD103/CD20 fluorescent antibodies and imaged in vitro using KronoScan, demonstrating it’s ability to detect antibody labelled cells. We next instilled these pre-labelled cells into human lungs undergoing EVLV and confirmed they could still be visualised using both fluorescence intensity and lifetime imaging against background lung architecture. Finally, we instilled fluorescent CD69 and CD103/CD20 antibodies directly into the lung and were able to detect TRM/BRM following in situ labelling within seconds of direct intra-alveolar delivery of microdoses of fluorescently labelled antibodies. Discussion In situ, no wash, immunolabelling with intra-alveolar OEM imaging is a novel methodology with the potential to expand the experimental utility of EVLV and pre-clinical models.